Pengaruh Balanced Scorecard dan Komitmen Organisasi terhadap Kinerja Manajemen Pada Perusahaan PLTU Pangkalan Susu Operation and Maintenance Services Unit Langkat - Eli Tesalonica Sitepu; Ali Usman Siregar; Warsani Warsani (Universitas Medan Area, 2022)
The purpose of this study was to determine the effect of the balanced scorecard and organizational commitment on management performance at the PLTU Pangkalan Susu Operation and Maintenance Services Unit Langkat company. The type of research used by researchers in this study is the associative type. The sample in this study amounted to 40 respondents (Senior Manager, Manager, Assistant Manager) who work in Company Operations. The type of data in this research is the type of quantitative data. The source of data used in this study is the primary source. Data collection techniques used in this study used a collection technique with a questionnaire. The data analysis technique used in this study was IBM SPSS Statistics version 26.00. The results showed that the Balanced Scorecard had a positive and significant effect on Management Performance. Organizational Commitment has a positive and significant effect on Management Performance. Balanced scorecard and organizational commitment have a positive and significant impact on Management Performance at the PLTU Pangkalan Susu Operation and Maintenance Services Unit Langkat Company.